'An otherness that cannot be sublimated': Shades of Frankenstein in Penny Dreadful and Black Mirror. (June 2018) - Artt, Sarah
Abstract : This article traces some of the legacies of the Frankenstein narrative as it appears in the television series Penny Dreadful and Black Mirror . Both series deploy Frankenstein themes to explore the relationship between gender and technology. Drawing on the work of Julia Kristeva and others, it argues that the hybrid bodies of Lily in Penny Dreadful and Ash in the Black Mirror episode 'Be Right Back' are powerful examples of abjection and how it works differently across genders. Both series are part of a continuous reworking of Shelley's text that demonstrates we are still living in the age of Frankenstein: a period of fascination with the body, gender and scientific innovation epitomised by the themes of Shelley's story.